Efficient use of social media during the avian influenza A(H7N9) emergency response - Fung, Isaac Chun-Hai; Wong, Karen K. (Western Pacific Surveillance and Response, 2013)
We describe how CDC epidemiologists used social media to follow official outbreak information released by WHO and China during the H7N9 outbreak. We discuss why Twitter and weibo are useful tools for epidemiologists in emergency response.